AN ANALYSIS OF SLANG WORDS USED IN SOCIAL MEDIA - Wahyu Trimastuti (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2017)
Human needs a means of communication to fulfill their social needs. To support communication easier, electronic media is used, such as television, radio, telephone, and handphone. Electronic media provide information can be understood more easily and instanly. The development of era has been influence in communication and interaction way. In this case, language which be used also influenced. Nowadays, many of slang word used in communication. Slang is a language variety which are informal which used to communication more easily and instanly in social group.The objectives of research is to inform about slang word (in this case ‘alay language’) which complicated with standard of Indonesia language. Therefore, the use of alay language is worried because it has many errors in Indonesia language. And, it can damage the standard of Indonesia language. The method used in this research is qualitative method, writer select descriptive techniques to analyze the data. Data obtained came from BlacBerry messenger, twitter, instragram, path, line and facebook. To colect data, writer used the method of observation. The writer found that in Alay ‘Alay’ is one of slang language that used in talk between teenagers. It can be understood by certain group particularly group who use ‘alay’ language. ‘Alay’ language for communication has many errors in Bahasa Indonesia. Alay language in social media can be minimized in order to avoid misunderstanding in delivering message.Key Words: communication, ‘slang’ language, alay, social media